2021
DOI: 10.1186/s40560-021-00530-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-citation policies and journal self-citation rate among Critical Care Medicine journals

Abstract: Background Inappropriate authors’ self-citation (A-SC) is a growing mal-practice possibly boosted by the raising importance given to author’s metrics. Similarly, also excessive journals’ self-citation (J-SC) practice may factitiously influence journal’s metrics (impact factor, IF). Evaluating the appropriateness of each self-citation remains challenging. Main body We evaluated the presence of policies discouraging A-SC in Critical Care Medicine (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
1
8
3
Order By: Relevance
“…In this study, we found that Respiratory System journals had a low prevalence of A-SCs policies (~14%). This prevalence is identical to Anesthesiology journals [4] but lower than in Critical Care Medicine [5] and General Surgery [6] journals (22% and 25%, respectively), as shown in previously conducted analyses on A-SCs and J-SC rates in other medical categories.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, we found that Respiratory System journals had a low prevalence of A-SCs policies (~14%). This prevalence is identical to Anesthesiology journals [4] but lower than in Critical Care Medicine [5] and General Surgery [6] journals (22% and 25%, respectively), as shown in previously conducted analyses on A-SCs and J-SC rates in other medical categories.…”
Section: Discussionsupporting
confidence: 78%
“…The other side of self-citation malpractice is represented by J-SC, which may hinder the attempt to increase the journal IF. The J-SC rate was highly variable in Respiratory System journals, similarly to Anesthesiology (1-37%), Critical Care Medicine (0-35%) and General Surgery (0-31%) journals [4][5][6]. When comparing groups, we could not find a significant influence of A-SC policies on IF and J-SC rates.…”
Section: Discussionmentioning
confidence: 63%
“…A possible reason for our results could also be self-citation by authors and journals. To self-promote and increase the impact factor, some journal may have a high self-citation rate [33], especially among journals with low impact factors [34]. Some authors may take the initiative to cite studies published in the same journal to improve the chance of being accepted, and retracted articles may be cited by mistake.…”
Section: Discussionmentioning
confidence: 99%
“…However, self-citations can also be manipulated by the researchers to affect their influence and recognization. Due to the potential role of author self-citations in citation manipulation, the accurate utilization of self-citations has become an ethical concern and there is ongoing effort to better delineate the self-citation-based ethical misconducts in the academic era ( 9 , 10 , 11 , 12 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%